ECONOMETRIC MODEL FOR ECONOMIC VALUETION OF ECOTOURISM: TINGO MARÍA NATIONAL PARK - Morales y Chocano, Luis (2016)
The research was carried out in the Tingo María National Park and aimed to identify the determinants of the economic value of ecotourism, generated by “Cueva de las Lechuzas”. In order to verify the hypothesis that the socioeconomic aspects and the choice of the environmental services of visitors influence the economic value of ecotourism, a survey was carried out. A binary-choice microeconometric model was estimated, to determine the convenience of entry payment to the tourist attraction, achieving to establish that both socioeconomic aspects and environmental services influence the intention of payment. Regarding the characteristics of environmental services choice, it was found that the main reason to visit to this important resource, corresponds to the invitation of a friend and / or family member who previously visited the area. Regarding the destination of the visit, most respondents agree that the Cueva de las Lechuzas visit is not the only destination. Finally, the majority of visitors classifies it as recreational tourism, and the disposition to pay is three soles per national visitor and five soles per foreigner.